Advances and challenges in electrochemical CO2 reduction processes: an engineering and design perspective looking beyond new catalyst materials. Issue 4 (19th December 2019) - Garg, Sahil; Li, Mengran; Weber, Adam Z.; Ge, Lei; Li, Liye; Rudolph, Victor; Wang, Guoxiong; Rufford, Thomas E.
Abstract : This review of design and operating conditions of electrochemical CO2 reduction covers electrolytes, electrodes, reactors, temperature, pressure, and pH effects. Abstract : Electrochemical CO2 reduction (CO2 R) is one of several promising strategies to mitigate CO2 emissions. Electrochemical processes operate at mild conditions, can be tuned to selective products, allow modular design, and provide opportunities to integrate renewable electricity with CO2 reduction in carbon-intensive manufacturing industries such as iron and steel making. In recent years, significant advances have been achieved in the development of highly efficient and selective electrocatalysts for CO2 R. However, to realize fully the potential benefits of new electrocatalysts in low cost, large scale CO2 R electrolyzers requires advances in design and engineering of the CO2 R process. In this review, we examine the state-of-the-art in electrochemical CO2 R technologies, and highlight how the efficiency of CO2 R processes can be improved through (i) electrolyzer configuration, (ii) electrode structure, (iii) electrolyte selection, (iv) pH control, and (v) the electrolyzer's operating pressure and temperature. Although a comprehensive review of catalytic materials is beyond this review's scope, we illustrate how other engineering and design decisions may also influence CO2 R reaction pathways because of effects on mass transfer rates, the electrode surface chemistry, interactions with intermediate reaction species, and rates of charge transfer.